The Contradiction of Indonesia’s Developmentalism Agenda and Environmental Policies in Jokowi’s Administration - Kuswardini, Seftina; Megan Alvira Putri; Santoso, Yohanes William (Global Strategis, 2025)
One of the subjects in the global environmental crisis study is how environmental changes create vulnerability among society, thus raising human security issues. The flood disaster in Kalimantan in January 2021 is a clear example that illustrates the impact of environmental change on human security. Furthermore, Indonesia's case is interesting because, amid the current environmental crisis, Indonesia still has an ambitious developmentalism agenda. However, Indonesia has also demonstrated environmental policies through an active role in environmental protection agreements at the international level, policy formulation at the domestic level, and implemented concrete actions such as corrective action plans. This paper discusses the contradiction between the developmentalism agenda and Indonesia's environmental protection policies in the era of President Jokowi. The author argues that amidst the environmental crisis and threats to human security, Jokowi's developmental agenda shows ambitious goals. However, at the same time, this agenda is not balanced with strong environmental protection measures. Therefore, the existing environmental protection policies and efforts are considered only as government efforts to legitimize the developmentalism agenda. Keywords: environmental crisis, human security, Indonesia, developmentalism, environmentalism Salah satu bahasan dalam kajian krisis lingkungan global adalah bagaimana perubahan alam dapat berdampak pada kerentanan masyarakat sehingga memunculkan isu keamanan manusia. Bencana banjir di Kalimantan pada Januari 2021 merupakan salah satu contoh nyata yang menggambarkan dampak perubahan alam terhadap keamanan manusia. Lebih jauh lagi, Indonesia merupakan negara yang menarik untuk dibahas karena di tengah krisis lingkungan yang ada, Indonesia masih memiliki agenda developmentalisme yang ambisius. Walaupun demikian, Indonesia juga menunjukkan kebijakan environmentalisme melalui peran aktif dalam kesepakatan perlindungan lingkungan di tingkat internasional, penyusunan kebijakan di tingkat domestik, hingga tindakan konkret seperti corrective action plan. Tulisan ini membahas tentang kontradiksi antara agenda developmentalisme dan kebijakan perlindungan lingkungan Indonesia di era Presiden Jokowi. Penulis berargumen bahwa di tengah krisis lingkungan dan ancaman terhadap keamanan manusia yang ada, agenda developmentalisme Jokowi menunjukkan kesan ambisius. Namun di saat yang bersamaan, agenda tersebut tidak diimbangi dengan upaya perlindungan lingkungan yang tegas. Kebijakan dan upaya perlindungan lingkungan yang ada akhirnya terkesan hanya sebagai upaya pemerintah untuk melegitimasi agenda developmentalisme. Kata-kata kunci: krisis lingkungan, keamanan manusia, Indonesia, developmentalisme, environmentalisme